2003
DOI: 10.1016/s1010-7940(03)00115-5
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in plasma antioxidant and lipid peroxidation levels following coronary artery bypass surgery: a complex response

Abstract: TPAC is suppressed for 72 h following CABG. TPAC depression may be involved in the mechanism of lipid peroxidation and is influenced by clinical factors known to be related to post CABG morbidity and mortality, like low ejection fraction and long ischaemic times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
2
16
0
1
Order By: Relevance
“…Increased venous concentration of malonyldialdehyde has been found in patients subjected to cardiac surgery [10,11,44]. However, malonyldialdehyde concentrations in systemic blood may reflect changes unrelated to cardiac oxidative stress (prostanoid synthesis [45], activity of aldehyde-dehydrogenase [35] and aldosereductase [36]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased venous concentration of malonyldialdehyde has been found in patients subjected to cardiac surgery [10,11,44]. However, malonyldialdehyde concentrations in systemic blood may reflect changes unrelated to cardiac oxidative stress (prostanoid synthesis [45], activity of aldehyde-dehydrogenase [35] and aldosereductase [36]).…”
Section: Discussionmentioning
confidence: 99%
“…However, malonyldialdehyde concentrations in systemic blood may reflect changes unrelated to cardiac oxidative stress (prostanoid synthesis [45], activity of aldehyde-dehydrogenase [35] and aldosereductase [36]). Indeed, surgery itself (independent of cardioplegic arrest/reperfusion) may induce systemic lipid peroxidation [18,44,46]. To specifically investigate lipid peroxidation at cardiac level, we simultaneously measured lipid peroxides in the blood entering the heart and in the coronary sinus effluent, and therefore could establish that no cardiac release of lipid peroxides occurred.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,22 Oxidative stress results from an imbalance between local antioxidant defences and formation of reactive oxygen derived free radicals, which are generated and released by activated inflammatory cells. ROS are highly reactive and can induce lipid peroxidation (oxidation of membrane phospholipids) and the accumulation of their products including MDA, 7,16,23,24 4-hydroxy-2-nonenal, acrolein, hydroperoxides 6 and F2-isoprostanes 7,10,14 acts as an indirect measure of free radical activity. 8,9,25 Experiments have demonstrated that oxidative stress may cause alterations in essential components of the lung, contributing to pathological abnormalities and functional changes.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 To counterbalance this sequence of events and diminish oxidative injury, several studies have investigated and recommended the use of antioxidant supplements. 18 To prevent elevations in proinflammatory cytokines and complement activation during cardiac surgery, several agents viz.…”
Section: Discussionmentioning
confidence: 99%